A prospective cohort study examining the associations of dietary calcium intake with all-cause and cardiovascular mortality in older Chinese community-dwelling people. - Ruth Chan (Public Library of Science (PLoS), 2013)
Background Most epidemiological studies of calcium intake and mortality risk have been conducted in populations with moderate to high calcium intake, and limited studies have focused on populations with low habitual calcium intake (i.e., mean dietary calcium intake <700 mg/d). Objective This study investigated the association between dietary calcium intake and death from all causes and cardiovascular disease in Chinese population with low habitual calcium intake. Design Data from 3,139 Chinese men and women in a population-based prospective cohort study, aged >=65 years and free of heart diseases or stroke at baseline, were analyzed. Primary outcome measures, identified from the death registry, were death from all causes and cardiovascular disease. Dietary calcium intake assessed using a validated food frequency questionnaire was categorized into sex-specific quartiles. Data on use of supplemental calcium (yes or no) including individual calcium supplements and other calcium containing supplement were collected. Cox regression models adjusted for demographic and lifestyle variables were used to estimate hazard ratios (HRs) and 95% confidence intervals (CI). Results During a median of 9.1 years of follow-up, 529 all-cause deaths (344 men, 185 women) and 114 (74 men, 40 women) deaths from cardiovascular disease were identified. An inverse trend between dietary calcium intake and mortality was observed. Compared with the lowest quartile (<458 mg/d for men, <417 mg/d for women), the highest quartile of dietary calcium intake (>762 mg/d for men, >688 mg/d for women) had a significantly reduced risk of all-cause mortality (multivariate HR=0.63, 95% CI=0.49-0.81, P(trend)<0.001) but an insignificant decreased risk of cardiovascular mortality (multivariate HR=0.70, 95% CI=0.41-1.21, P(trend)=0.228). Similar inverse association was observed when the analyses were stratified on calcium supplemental use. Conclusions Higher intake of dietary calcium was associated with reduced risk of all-cause mortality and possibly cardiovascular mortality in Chinese older people with low habitual calcium intake.